COVID19-Associated Aspergillosis in the ICU Settiing (Revista de Medicina Clinica, 2022)
Editorial letter presented volume 6 issue 1 of Revista de Medicina Clínica about Pulmonary Aspergillosis as a complication related to SARS-COV2 infection.
Keywords: COVID-19; Pulmonary Aspergillosis; Intensive Care Unit